HAK UPAH TERHADAP TENAGA KERJA YANG DIRUMAHKAN AKIBAT PANDEMI COVID-19 BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2013 (STUDI KASUS : PUTUSAN NOMOR 60/PDT.SUS-PHI/2020.GTO - Femela Yosefin Gloria Untu; Gunardi Gunardi (Fakultas Hukum Universitas Tarumanagara, 2022)
During the Covid-19 Pandemic Period there were many problems experienced by theworkforce, especially related to the provision of wages or salaries. In Decision No.60/Pdt.sus-PPHI/2020/PN.Gto, which made the defendant consider the situation in a pandemicas impossible for the defendant to get rid of, therefore the elements contained in article 93paragraph 2 letter f were not achieved. Therefore, there is no obligation for employers toprovide compensation to workers who have been laid off due to the COVID-19 pandemic.This creates legal uncertainty between the Manpower Act and the Minister of ManpowerDecree No. M/3HK.04/III/2020 which regulates the provision of wages must be based on anagreement between the company and the workers. Aan Supu has worked as an employee ofPT. Paradise Cipta Persada with a working period of 6 years, and was sent home due to thecovid-19 pandemic then he did not get the right to his wages (salary) while he was home. AanSupu filed a lawsuit to the Industrial Relations Court at the Gorontalo District Court, but thelawsuit was completely rejected by the panel of judges. This research is normative withanalytical descriptive nature. The type of data used in this research is secondary whichincludes primary legal materials and secondary legal materials. The results of the writing showthat when viewed from Law No. 13 of 2013 concerning employment. The author concludesthat because of that the rights and obligations of each party must be fulfilled until there is adecision from the Industrial Relations Court Institution, in which workers will get legalprotection by obtaining wage rights, or service fees.